Silver carboxylate-TiO2/polydimethyl siloxane is a safe and effective antimicrobial with significant wound care potential - Allu, Sai; Whitaker, Colin; Stone, Benjamin; Vishwanath, Neel; Clippert, Drew; Jouffroy, Elia; Antoci, Valentin; Born, Christopher; Garcia, Dioscaris R. (OTA international : the open access journal of orthopaedic trauma, 2024)
AbstractIntroduction:With the rise in antibiotic resistance, new methodologies are needed to combat musculoskeletal infections. Silver is an antimicrobial that can be synthesized in different forms, but its pharmacokinetics are difficult to control. This study details the antibacterial efficacy and cellular cytotoxicity of a formulation consisting of silver carboxylate (AgCar) released through a titanium dioxide/polydimethylsiloxane matrix with a predictable release profile on Pseudomonas aeruginosa, Acinetobacterium baumannii, and human-derived primary osteoblasts.Methods:Through an Institutional Animal Care and Use Committee and IRB-approved protocol, AgCar was applied to live Yucatan porcine skin and histologically analyzed for skin penetration. Graphite Furnace Atomic Absorption Spectroscopy (GFAAS) was used to measure elution of AgCar. Dose-response curves were generated through optical density to assess potency. Finally, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was used to quantify the cellular cytotoxicity of the novel formulation. The results were subject to statistical analysis using analysis of variance and post hoc Tukey tests.Results:The silver carboxylate coating demonstrated deep penetration into the epithelium at the level of the deep pilosebaceous glands in animal models. GFAAS testing demonstrated the extended elution profile of silver carboxylate over 96 hours, while 100% silver with no titanium dioxide-polydimethylsiloxane matrix fully eluted within 48 hours. 10x silver carboxylate demonstrated superior antimicrobial activity to antibiotics and other silver formulations and showed minimal cytotoxicity compared with other silver formulations.Discussion/Clinical Relevance:Current antimicrobial therapies in wound care and surgical antisepsis, such as chlorhexidine gluconate, have pitfalls including poor skin penetration and short duration of efficacy. The broad antimicrobial activity, extended elution, and deep skin penetration of this AgCar formulation show great promise for surgical site infection and wound care treatment. Novel technology to fight the growing threat of microbial resistance should be at the forefront of orthopaedic surgical site infection prevention and treatment.